Detection of 1014F kdr mutation in four major Anopheline malaria vectors in Indonesia - Syafruddin, Din (BioMed Central, 2010)
BACKGROUND: Malaria is a serious public health problem in Indonesia, particularly in areas outside Java and Bali. The spread of resistance to the currently available anti-malarial drugs or insecticides used for mosquito control would cause an increase in malaria transmission. To better understand patterns of transmission and resistance in Indonesia, an integrated mosquito survey was conducted in three areas with different malaria endemicities, Purworejo in Central Java, South Lampung District in Sumatera and South Halmahera District in North Mollucca. METHODS: Mosquitoes were collected from the three areas through indoor and outdoor human landing catches (HLC) and indoor restinging catches. Specimens were identified morphologically by species and kept individually in 1.5 ml Eppendorf microtube. A fragment of the VGSC gene from 95 mosquito samples was sequenced and kdr allelic variation determined. RESULTS: The molecular analysis of these anopheline mosquitoes revealed the existence of the 1014F allele in 4 major malaria vectors from South Lampung. These species include, Anopheles sundaicus, Anopheles aconitus, Anopheles subpictus and Anopheles vagus. The 1014F allele was not found in the other areas. CONCLUSION: The finding documents the presence of this mutant allele in Indonesia, and implies that selection pressure on the Anopheles population in this area has occurred. Further studies to determine the impact of the resistance allele on the efficacy of pyrethroids in control programmes are needed.